When mechanical stress matters: generation of polyploid giant cancer cells in tumor-like microcapsules - Antonelli, Yasmin; Krüger, René; Buehler, Adrian; Monavari, Mahshid; Fuentes-Chandía, Miguel; Colombo, Federico; Palmisano, Ralf; Boßerhoff, Anja K.; Kappelmann-Fenzl, Melanie; Schödel, Johannes; Boccaccini, Aldo R.; Selhuber-Unkel, Christine; et al. (Advanced functional materials, 2024)
Biofabrication techniques enable the performance of bioinspired three-dimensional (3D) matrices resembling primary tumors. To validate their reliability, embedded cells may express complex biophysical responses. Among others, the emergence of tumor heterogeneity and the generation of Polyploid Giant Cancer Cells (PGCC), as a result of the mechanical stress, are two of the most challenging hallmarks to resemble in vitro. Here, these phenomena are studied in cells cultured on two-dimensional (2D) flasks, in 3D spheroids, or immobilized within 3D polymer-based tumor-like microcapsules. These results show that cells cultured in 3D microcapsules exhibited an enhanced biomechanical heterogeneity, a higher number of PGCC, and an increased exertion of cell-matrix attachment forces with respect to the other two experimental conditions. Additionally, cells isolated from tumor-like microcapsules redistribute and align the cytoplasmatic protein Caveolin-1, and upregulate markers involved in cell proliferation (i.e., Ki67), metastasis (i.e., TGF-β1, TGF-β-R2), and epithelial to mesenchymal transition, to name a few. These hallmarks are barely described in the past as a result of the confinement and mechanical stress. Thus, in this work it is demonstrated that both the mechanical stress and confinement are required to stimulate cell polyploidy and biomechanical heterogeneity, which can be easily addressed by immobilizing breast cancer cells in tumor-like microcapsules.